OcupaMax: projeto de consultoria em ocupação de lazer e hotelaria - Mondini, Hiago Messias (Universidade Federal de São Carlos, 2024)
This course completion work aims to develop a consultancy that analyzes and presents effective strategies to optimize and scale the occupation of idle spaces in commercial hotels and leisure spaces, with a focus on the development of a company specialized in the segment, called OcupaMax. The research covers theoretical aspects related to entrepreneurship, hotel management, occupancy strategies and commercial strategies in establishments in Sorocaba and the region. Furthermore, it recognizes the crucial role that specialized companies managed by tourism experts play in maximizing operational and financial efficiency in spaces that are susceptible to idleness on weekdays and off-season, thus suggesting a business plan to increase occupancy potential of said establishments.
OcupaMax: leisure and hotel occupancy consultancy project
OcupaMax: レジャーおよびホテル占有コンサルティング プロジェクト
Keywords: Hospedagem; Consultoria; Estratégias de Ocupação; Ociosidade; Empreendedorismo; Fluxo Turístico; OcupaMax; Turismo; Lazer; Leisure; Idleness; Tourism Flow; Entrepreneurship; Occupancy Strategies; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::MERCADOLOGIA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; CIENCIAS SOCIAIS APLICADAS::TURISMO